Asian Interfaith Dialogue : Perspectives on Religion, Education and Social Cohesion - Alatas, Syed Farid; Ghee, Lim Teck; Kuroda, Kazuhide (Singapore: Centre for Research on Islamic and Malay Affairs and the World Bank, 2013)
The events of the last few years have directed even more attention to the relationships among religion, education and social cohesion in the context of development in Asia. There is, therefore, a need to consider the combined role of religion and education in fostering a more holistic form of development without concurrently fanning flames of ethnic, religious and other kinds of conflicts. This book discusses the relationship between religion, the role of education in generating social capital and its impact on the development of society. It draws on papers presented at an interfaith workshop co-hosted by the World Bank and the Centre for Research on Islamic and Malay Affairs (RIMA). The dialogue took place in Singapore on 27-28 October 2001, with the participation of some 50 experts from Indonesia, Japan, Malaysia, the Philippines, Singapore and Thailand. The book describes the rich group of partners associated with this dialogue, their call to move beyond the discourse of dialogue and the imperative to start practicing it. It conveys an effort to learn from both sides. It lays out the debates of scholars who see education as a major instrument for fostering knowledge and skills -- with the purpose of improving knowledge sharing, teaching methodologies, and bolstering mutual development efforts.